Celebrity Endorsements in Politics: a Systematic Literature Review - Wijaya, Lukita (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
This research utilizes the Systematic Literature Review (SLR) method to analyze the development of the concept of celebrity endorsement in politics and its influence on voter preferences. The results of the analysis indicate that celebrities play a significant role in shaping the political preferences of their fans. Initially unidimensional, the concept has evolved into a multidimensional phenomenon. The popularity of celebrities, originally limited to products and brands, now extends to the political realm, creating a convergence between the entertainment and political spheres. The research focuses on the ability of celebrity endorsers to alter consumer attitudes, particularly in the context of political marketing. The conclusion of this study affirms that celebrity participation in politics is increasingly relevant, enhancing potential support, and establishing a more crucial role in the political arena.